Incidental Adrenal Nodules and Masses: The Imaging Approach - J. Willatt; S. Chong; J. A. Ruma; J. Kuriakose (International Journal of Endocrinology)
Adrenal nodules are detected with increasing frequency. The National Institute of Health (NIH), American College of Radiology (ACR), and the American Association of Clinical Endocrinologists and American Association of Endocrine Surgeons (AACE/AAES) have produced guidelines for the management of incidental adrenal nodules. This review provides a summary of the consensus radiologic approach to these nodules.